ANALISA PENERAPAN SISTEM INFORMASI PERPUSTAKAAN UNIVERSITAS INDO GLOBAL MANDIRI - Terttiaavini Terttiaavini (UNIVERSITAS INDO GLOBAL MANDIRI)
Increasing student achievement is not only dependent on science is taught by lecturers, but with a high interest, will be able to broaden their field of study miliki.Untuk increase reading interest of students, a university must have a good library information system. Library is one of the important unit in the establishment of a college. Library information system supported by good data processing, SOP good and also good infrastructure (standard), will have a significant impact on the progressive increase in interest in reading Mahasiswa.Suatu universities that have implemented the library information system, should be able to ensure that the systems supporting applications information library, actually still running well. Measurement of whether or not the system, carried out by analyzing the indicators - indicators of success of the system. Indicators of success is measured by the method menggunan COBIT Framework. COBIT Framework has four domains. The domain used to measure library information system is the delivery and support (delivery and Support). By calculating the maturity value, it can be determined whether good or bad condition of the Library Information System. The case study of this research takes the object of study in the University of Indo Global Mandiri. The results of this study, researchers in the form of an analysis of the library information system UIGM today, and suggestions for the leadership of Higher Education for the development of library information system better, in order to meet the needs of the organization and its stakeholders.